(untitled) (World Science, 2020)
The article provides relevant data on the features of the microbiocenosis of the genital tract of women of fertile (childbearing) age. It is known that the microbiocenosis of the reproductive tract begins to form in a newborn girl 3-4 hours after birth, and throughout the neonatal period it is similar to the microbiocenosis of a woman of reproductive age. The key role in maintaining the health and normal functioning of the microbiocenosis of the female reproductive sphere belongs to lactobacilli, as the main component of the vaginal microflora. Microbiological disorders in this biotope usually lead to the development of chronic diseases of the pelvic organs. Based on recent studies on the relationship between the disturbance of the vaginal microflora with intestinal dysbiosis and chronic diseases of the nasopharyngeal biotope, it is relevant to study the quantitative and qualitative composition of the microflora of the reproductive tract, especially in pregnant women and after abortion (artificial termination of pregnancy) of women of fertile age in Uzbekistan.